Influence of magnetic fluid evaporation on pressure resistance of magnetic fluid seal - Yu, Wenjuan; Li, Decai; Zang, Guobao; Wang, Deyi; Zhang, Zhili (Frontiers in Materials, 2022)
Magnetic fluid seals have the advantages of zero leakage, long life, simple structure and high reliability, and have become one of the most widely used applications of magnetic fluids. In this paper, the effect of magnetic fluid evaporation on the pressure resistance of magnetic fluid seals is studied. In terms of theory, through theoretical calculation and simulation analysis, a calculation method for the pressure resistance of magnetic fluid seals is established. In terms of experiments, firstly, five groups of control groups were set up to conduct evaporation experiments under the same conditions, and magnetic fluids with different evaporation rates were obtained; Secondly, the performance of magnetic fluids with different evaporation rates was tested, and the flow curves, viscosity-temperature curves, and magnetic-viscosity curves of magnetic fluids were obtained respectively, and the effect of evaporation on the performance of magnetic fluids was analyzed; Finally, magnetic fluid sealing experiments with different evaporation rates were carried out. It is found that evaporation increases the pressure resistance of static seal to a certain extent, which is of great significance.